2005
DOI: 10.1086/432722
|View full text |Cite
|
Sign up to set email alerts
|

Enterohemorrhagic Escherichia coli in Human Infection: In Vivo Evolution of a Bacterial Pathogen

Abstract: We demonstrate the loss of a critical bacterial virulence factor from pathogens during very brief intervals in the human host. These genetic changes have evolutionary, diagnostic, and clinical implications. Generation of stx- mutants might contribute to subclonal evolution and evolutionary success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
113
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(119 citation statements)
references
References 49 publications
6
113
0
Order By: Relevance
“…One can suggest that these differences may probably be due to the presence or the absence of the stx bacteriophage. The lack of a bacteriophage that originated a distinct PFGE pattern was reported by other investigators in O26 and O157:H7 STEC strains (25,28). Similarly to serogroup O111, PFGE patterns clearly classified Brazilian O157 strains in two main groups.…”
Section: Discussionsupporting
confidence: 63%
“…One can suggest that these differences may probably be due to the presence or the absence of the stx bacteriophage. The lack of a bacteriophage that originated a distinct PFGE pattern was reported by other investigators in O26 and O157:H7 STEC strains (25,28). Similarly to serogroup O111, PFGE patterns clearly classified Brazilian O157 strains in two main groups.…”
Section: Discussionsupporting
confidence: 63%
“…The absence of stx-negative/eae-positive E. coli O111 isolates in the HUS patients may be explained by the fact that a majority of the EHEC O111 isolates possessed stx 1 solely or in combination with stx 2 (13), and the Stx1 prophage of EHEC O111 is thought to be defective, resulting in immobilization and stability in the EHEC chromosome (41). In contrast to a previous investigation (39) subcultures. Ten O111 colonies (1 to 10) isolated from a stool specimen were picked, and each colony was spread on a TSA plate (A).…”
Section: Discussionmentioning
confidence: 59%
“…Several reports have identified EHEC-associated HUS cases that no longer shed EHEC but do shed stx-negative EHEC organisms that presumably lost stx during infection (18,(37)(38)(39). Stx is the most important EHEC virulence factor, causing the specific clinical features of EHEC infection (1-4).…”
Section: Discussionmentioning
confidence: 99%
“…This was similar to the findings of Kozub-Witkowski et al [35], who molecularly identified eight strains that belonged to classical EHEC serotypes and were stx genes negative. This is not surprising, as there is still a possibility that these strains might acquire stx genes by horizontal transfer with a subsequent disease burden to humans [36], or they may have originated as EHEC strains and then lost phage-encoded stx genes [37].…”
Section: Discussionmentioning
confidence: 99%